2010
DOI: 10.1172/jci41709
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II sustains brain inflammation in mice via TGF-β

Abstract: The renin-angiotensin-aldosterone system (RAAS) is a key hormonal system regulating blood pressure. However, expression of RAAS components has recently been detected in immune cells, and the RAAS has been implicated in several mouse models of autoimmune disease. Here, we have identified Ang II as a paracrine mediator, sustaining inflammation in the CNS in the EAE mouse model of MS via TGF-β. Ang II type 1 receptors (AT1Rs) were found to be primarily expressed in CNS-resident cells during EAE. In vitro, astrocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
159
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 188 publications
(167 citation statements)
references
References 49 publications
5
159
1
2
Order By: Relevance
“…Even more striking, the administration of the ACE inhibitor lisinopril after the establishment of EAE actually reversed the severity of animal paralysis. Both in their original study and in a followup investigation, this group identified angiotensin II-induced expression of transforming growth factorb as being important in the pathogenesis of EAE (Lanz et al, 2010). Several other studies have demonstrated a role of ACE and angiotensin II in models of autoimmunity, including rheumatoid arthritis and experimental autoimmune uveoretinitis (Dalbeth et al, 2005;Sagawa et al, 2005;Okunuki et al, 2009).…”
Section: H Myelopoiesismentioning
confidence: 98%
“…Even more striking, the administration of the ACE inhibitor lisinopril after the establishment of EAE actually reversed the severity of animal paralysis. Both in their original study and in a followup investigation, this group identified angiotensin II-induced expression of transforming growth factorb as being important in the pathogenesis of EAE (Lanz et al, 2010). Several other studies have demonstrated a role of ACE and angiotensin II in models of autoimmunity, including rheumatoid arthritis and experimental autoimmune uveoretinitis (Dalbeth et al, 2005;Sagawa et al, 2005;Okunuki et al, 2009).…”
Section: H Myelopoiesismentioning
confidence: 98%
“…EGFR signaling is required for TLR4-mediated activation of NF-B in response to lipopolysaccharide (20), and its activation by ANG II can occur within a similar time course (in minutes) as the effect we describe here for ANG II-TLR4-ROS production. Another possibility is that ANG II induces the upregulation and activation of the cytokine transforming growth factor-␤ by trombospondin-1 (36), which, in turn, activates TLR4 pathways in macrophages to induce TNF-␣ production (42). Clearly, future studies are warranted to more precisely characterize the signaling mechanisms underlying the ANG II-AT 1a R-TLR4 cross talk in mediating microglial ROS production in the PVN.…”
Section: Tlr4 In Microglia Is Involved In Ang Ii-mediated Ros Within mentioning
confidence: 99%
“…Indeed, these analyses revealed a more complex inhibition of leukocyte transendothelial migration pathways involving the suppression of additional key targets such as the Rho GTPase family member Rac1, which is induced by PKCβ (26) and has been shown to be critically involved in immunomodulatory efficacy of IFN-β in EAE (27), or the Rap guanine nucleotide exchange factor (GEF) 3 (Rapgef3), which is critically involved in the inflammatory vascular permeability (28). In addition, there was down-regulation of the transforming growth factor (TGF)-β pathway, which is induced during endothelial inflammation via PKCβ (29), and which is-when active in the CNS during autoimmune neuroinflammation-critical for the recruitment of encephalitogenic T cells (30,31) (Fig. S4).…”
mentioning
confidence: 99%